Investigating the role of elements of natural environment recreated in the clinical setting for stress reduction - Galimova, Gulnara (2018)
It has been shown in environmental psychology research that a natural environment can promote stress reduction which could be used for relaxation purposes in music therapy. However, therapy is normally conducted in clinical settings, and therapists do not always have the option to take patients outdoors. In this study, the elements of the natural environment were recreated in the clinical setting to investigate their role in stress reduction during the relaxation music listening session. The presence of natural elements were expected to lead to greater stress reduction. Stress levels were evaluated subjectively with visual analogue scales and objectively via the heart rate variability. Results revealed that in presence of the natural elements participants reported feeling less stressed, but HRV data does not fully support this finding. Also, a trend of improved night sleep quality after the “Nature” intervention was found. Overall, more stressed participants benefited more from the “Nature” condition, but due to the small sample size the results cannot be generalized and further investigation is needed. Finally, a mismatch between the subjective and objective data was pointed out, and its meaning was discussed.